PENGARUH FASILITAS KANTOR DAN DISIPLIN KERJA TERHADAP KINERJA PEGAWAI DI KANTOR DESA PELAWAD KABUPATEN SERANG - Linda Dwi Astuti; Lismiatun (Journal of Research and Publication Innovation, 2025)
This study aims to analyze the influence of office facilities partially on employee performance at the Pelawad Village Office, Serang Regency, to analyze the influence of work discipline partially on employee performance at the Pelawad Village Office, Serang Regency, to analyze the influence of office facilities and work discipline simultaneously on employee performance at the Pelawad Village Office, Serang Regency. The methodology used is quantitative descriptive using multiple linear regression. The results of the study showed 1) the results of the t-test showed a sig value for the influence of office facilities (X1) on employee performance (Y) was 0.041 <0.05, and the t-count value> t-table, which was 2.095> 2.007. So the office facilities variable (X1) has a significant effect on employee performance, 2) the results of the t-test showed a sig value for the influence of work discipline (X3) on employee performance (Y) was 0.013 <0.05, and the t-count value> t-table, which was 2.570> 2.007. So the work discipline variable (X3) has a significant effect on employee performance, 3) The results of the F test show a calculated F value of 13.708> 3.18 with a significance of 0.000 <0.05, so it can be stated that this hypothesis (Ha) is accepted. Simultaneously, the independent variables of this study, namely office facilities and work discipline, have a significant effect on the dependent variable of employee performance